Pengaruh Kualitas Pelayanan dan Citra Merek terhadap Loyalitas Pelanggan Melalui Kepuasan Pelanggan di Byurger Coffee Menteng - Yanuar Febriansyah; Yosafat Puji Hastoko (J-CEKI : Jurnal Cendekia Ilmiah, 2023)
The purpose of this study is to analyze the effect of service quality and brand image on customer loyalty through customer satisfaction, both directly and indirectly in the context of a business engaged in the culinary field. The instrument was developed using a Likert scale. Respondents were 80 consumers and 30 respondents to test the validity and reliability. This study uses a quantitative method, using Path analysis. The results of this study indicate a direct effect of the variables Service Quality, Brand Image, and Customer Satisfaction on the Customer Loyalty variable. The indirect effect of the variables of Service Quality and Brand Image affects Customer Loyalty through Customer Satisfaction. Kata kunci: Kualitas Pelayanan; Citra Merek; Kepuasan Pelanggan; Loyalitas Pelanggan.